Auditoría de control interno al área de créditos y cobranzas del almacén créditos Innova del cantón La Maná, período 2012 - Guerrero Romero, Diego Alberto (2015)
This research was conducted in Canton La Maná order to establish the incidence of internal control audit in the area of credit and collections Warehouse Credits Innova, 2012. For this period the level of compliance was analyzed Laws and Regulations company, minutely examining the level of confidence of financial information. Which allowed Check the level of compliance that occurs in the operations of the Department of Credit and Collection Warehouse Credits Innova. For the development of internal control COSO I will apply the audit process is conducted in phases including the breakdown of the activities carried out in compliance with the review of the working papers thereof that are established with regulations is force as NIAS and IFRS in developing this process no experimental design and exploratory research was used because it is considered that the subject is poorly investigated so it requires finding information on primary and secondary sources , further used the descriptive model that facilitated know in detail the characteristics of the company , its management and be able to measure their level of compliance. Of the same way it finished concluding according to the objectives that thank to make the work of this investigation it can do it, and for last work we can give recomendations for the company.